233k views
2 votes
The work of a student to solve the equation 2(3x − 4) = 8 + 2x + 4 is shown below:

Step 1: 2(3x − 4) = 8 + 2x + 4
Step 2: 5x − 6 = 12 + 2x
Step 3: 5x − 2x = 12 + 6
Step 4: 3x = 18
Step 5: x = 6

In which step did the student first make an error and what is the correct step?

Step 2; 6x − 6 = 2(6 + x + 2)
Step 2; 6x − 8 = 12 + 2x
Step 3; 5x − 2x = 12 − 6
Step 3; 5x + 2x = 12 + 6

User Rgenito
by
5.6k points

1 Answer

7 votes

Answer:

step 2; 6x-8=12+2x; she added instead of multiplying

User Vivek Raskar
by
5.6k points